Kinome-Wide RNAi Screen Uncovers Role of Ballchen in Maintenance of Gene Activation by Trithorax Group in Drosophila - Khan, Muhammad Haider Farooq; Akhtar, Jawad; Umer, Zain; Shaheen, Najma; Shaukat, Ammad; Munir, Muhammad Shahbaz; Mithani, Aziz; Anwar, Saima; Tariq, Muhammad (Frontiers in Cell and Developmental Biology, 2021)
Polycomb group (PcG) and trithorax group (trxG) proteins are evolutionary conserved factors that contribute to cell fate determination and maintenance of cellular identities during development of multicellular organisms. The PcG maintains heritable patterns of gene silencing while trxG acts as anti-silencing factors by conserving activation of cell type specific genes. Genetic and molecular analysis has revealed extensive details about how different PcG and trxG complexes antagonize each other to maintain cell fates, however, the cellular signaling components that contribute to the preservation of gene expression by PcG/trxG remain elusive. Here, we report an ex vivo kinome-wide RNAi screen in Drosophila aimed at identifying cell signaling genes that facilitate trxG in counteracting PcG mediated repression. From the list of trxG candidates, Ballchen (BALL), a histone kinase known to phosphorylate histone H2A at threonine 119 (H2AT119p), was characterized as a trxG regulator. The ball mutant exhibits strong genetic interactions with Polycomb (Pc) and trithorax (trx) mutants and loss of BALL affects expression of trxG target genes. BALL co-localizes with Trithorax on chromatin and depletion of BALL results in increased H2AK118 ubiquitination, a histone mark central to PcG mediated gene silencing. Moreover, BALL was found to substantially associate with known TRX binding sites across the genome. Genome wide distribution of BALL also overlaps with H3K4me3 and H3K27ac at actively transcribed genes. We propose that BALL mediated signaling positively contributes to the maintenance of gene activation by trxG in counteracting the repressive effect of PcG.